Effects of IGF‐1 isoforms on muscle growth and sarcopenia. Issue 3 (5th April 2019) - Ascenzi, Francesca; Barberi, Laura; Dobrowolny, Gabriella; Villa Nova Bacurau, Aline; Nicoletti, Carmine; Rizzuto, Emanuele; Rosenthal, Nadia; Scicchitano, Bianca Maria; Musarò, Antonio
Abstract: The decline in skeletal muscle mass and strength occurring in aging, referred as sarcopenia, is the result of many factors including an imbalance between protein synthesis and degradation, changes in metabolic/hormonal status, and in circulating levels of inflammatory mediators. Thus, factors that increase muscle mass and promote anabolic pathways might be of therapeutic benefit to counteract sarcopenia. Among these, the insulin‐like growth factor‐1 (IGF‐1) has been implicated in many anabolic pathways in skeletal muscle. IGF‐1 exists in different isoforms that might exert different role in skeletal muscle. Here we study the effects of two full propeptides IGF‐1Ea and IGF‐1Eb in skeletal muscle, with the aim to define whether and through which mechanisms their overexpression impacts muscle aging. We report that only IGF‐1Ea expression promotes a pronounced hypertrophic phenotype in young mice, which is maintained in aged mice. Nevertheless, examination of aged transgenic mice revealed that the local expression of either IGF‐1Ea or IGF‐1Eb transgenes was protective against age‐related loss of muscle mass and force. At molecular level, both isoforms activate the autophagy/lysosome system, normally altered during aging, and increase PGC1‐α expression, modulating mitochondrial function, ROS detoxification, and the basal inflammatory state occurring at old age. Moreover, morphological integrity of neuromuscular junctions was maintained and preserved in both MLC/IGF‐1Ea and MLC/IGF‐1Eb mice during aging. These data suggest that IGF‐1 is a promising therapeutic agent in staving off advancing muscle weakness. Abstract : A summary of the molecular pathways responsible for the protective role of IGF‐1 isoforms against sarcopenia.